2009
DOI: 10.1007/s00441-009-0842-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone effects on Nav1.6 in tooth pulp, dental nerves, and alveolar osteoclasts of adult rats

Abstract: Dexamethasone causes extensive physiologic reactions including the reduction of inflammation and pain. Here, we asked whether it also affected dental or periodontal cells or dental innervation by altering voltage-gated sodium channel Na(v)1.6 immunoreactivity (IR) or neural synaptophysin. Daily dexamethasone (0.2 mg/kg) given for 1 week to rats caused 12-fold increased intensity of Na(v)1.6-IR in dendritic pulpal cells of normal molars and incisors compared with vehicle treatment. These cells also co-localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This antibody shows a wide range of species reactivity including humans [17,47]. The staining pattern seen in the current study is consistent with that seen previously [17,47,48]. …”
Section: Methodssupporting
confidence: 91%
“…This antibody shows a wide range of species reactivity including humans [17,47]. The staining pattern seen in the current study is consistent with that seen previously [17,47,48]. …”
Section: Methodssupporting
confidence: 91%
“…Since expression of VGSCs is an important property of excitable cells, the demonstration of Na V 1.6 expression in non-neuronal pulpal cells, such as pulpal immune cells, dendritic pulpal cells, and odontoblasts [29], has gathered a robust interest. In addition, electrophysiology, immunohistochemistry, RT-PCR, and in situ hybridization of odontoblasts differentiated from human dental pulp explants has revealed the expression and functionality of Na V 1.1, Na V 1.2, and Na V 1.3 [28].…”
Section: Voltage-gated Ion Channelsmentioning
confidence: 99%
“…In addition, voltage-gated and ligand-gated ion channels take important roles in tooth pain. Not only are various types of voltage-gated ion channels expressed in the trigeminal sensory nerve on common nerve cells, but they are also expressed in odontoblast cells [22,28,29,30,31,32]. Previous studies have indicated that small molecules, such as adenosine 5′-triphosphate (ATP), and their ionotropic receptors, the P2X family, play an important role in the sensory system for tooth pain [19,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone (Dex) causes extensive physiologic reactions including the reduction of inflammation and pain (Byers et al 2009). Dex is also known to enhance the osteoblastic phenotype in osteogenic cells, decrease collagenase expression, increase the PTH-mediated cAMP response, including PDL fibroblasts (Hayami et al 2007;Hakki et al 2009).…”
mentioning
confidence: 99%